New Insights Into the Metabolism and Role of Cytokinin N-Glucosides in Plants - Hoyerová, Klára; Hošek, Petr (Frontiers in Plant Science, 2020)
CCytokinin (CK) N-glucosides are the most abundant group of CK metabolites in many species; however, their physiological role in planta was for a long time perceived as irreversible storage CK forms only. Recently, a comprehensive screen showed that only vascular plants form CK N-glucosides in contrast to mosses, algae and fungi. The formation of CK N-glucosides as biologically inactive CK conjugates thus represents an evolutionarily young mechanism for deactivation of CK bases. Even though CK N-glucosides are not biologically active themselves due to their inability to activate the CK perception system, new data on CK N-glucoside metabolism show that trans-zeatin (tZ) N7- and N9-glucosides are metabolized in vivo, efficiently releasing free CK bases that are most probably responsible for the biological activities observed in a number of bioassays. Moreover, CK N-glucosides’ subcellular localization as well as their abundance in xylem both point to their possible plasma membrane transport and indicate a role also as CK transport forms. Identification of the enzyme(s) responsible for the hydrolysis of tZ N7- and N9-glucosides, as well as the discovery of putative CK N-glucoside plasma membrane transporter, would unveil important parts of the overall picture of CK metabolic interconversions and their physiological importance.